2014
DOI: 10.5430/ijhe.v4n1p77
|View full text |Cite
|
Sign up to set email alerts
|

Who Needs More Sleep? Comparing Undergraduate and Graduate Students' Sleep Habits in a National U.S. Sample

Abstract: Sleep disorders and deficits are a national U.S. health concern, and college students report more sleep difficulties than the general population. Most published studies examine college students as a homogenous population or focus on professional (e.g. medical) students. This study compares sleep patterns of undergraduate and graduate students from a national U.S. sample using the American College Health Association-National College Health Assessment (ACHA-NCHA) II survey. Graduate students on average reported … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 34 publications
1
6
0
Order By: Relevance
“…Another study suggested that students did not experience any significant changes in sleep quality because the quality of sleep in the respondents was already very poor ( Benham, 2020 ). This observation agreed with the results from other pre-pandemic studies on sleep quality in students ( Yang et al, 2003 ; Oswalt and Wyatt, 2014 ). It is probable that sleep quality is also dependent on the context of when it is measured; for example, longitudinal studies show an initial increase in sleep quality during the initial COVID-19 outbreak but a continuous decrease over time as the pandemic progressed ( Gusman et al, 2021 ).…”
Section: Introductionsupporting
confidence: 92%
“…Another study suggested that students did not experience any significant changes in sleep quality because the quality of sleep in the respondents was already very poor ( Benham, 2020 ). This observation agreed with the results from other pre-pandemic studies on sleep quality in students ( Yang et al, 2003 ; Oswalt and Wyatt, 2014 ). It is probable that sleep quality is also dependent on the context of when it is measured; for example, longitudinal studies show an initial increase in sleep quality during the initial COVID-19 outbreak but a continuous decrease over time as the pandemic progressed ( Gusman et al, 2021 ).…”
Section: Introductionsupporting
confidence: 92%
“…Even before the onset of the COVID-19 pandemic, undergraduate students experienced sleep problems (e.g., poor quality sleep, insomnia, insufficient sleep) 1,2 and mental health issues (e.g., anxiety, depression, stress) [3][4][5] that were negatively associated with academic achievement. 5,6 During the pandemic, students experienced additional stressors including the transition to online learning, potential loss of employment, and the threat of illness and death resulting from the COVID virus, among others.…”
Section: Introductionmentioning
confidence: 99%
“…Another study reported about 60% of students suffer from poor sleep quality [17]. Many graduate students balance their academic responsibilities with their additional priorities of work, and family, and might be stressed which could eventually affect their sleep quality [18].…”
Section: Introductionmentioning
confidence: 99%